Effect of Flow Versus Volume Incentive Spirometry on Chest Expansion in Coronary Artery Bypass Graft Surgery Patients: a Comparative Study - Kaushaljeet Gill (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Introduction Cardiac Surgeries lead to cardiac and pulmonary complications due to lack of lung inflation which include respiratory dysfunction, pleural effusion, lung collapse etc. Chest expansion measurements are used to evaluate the patient’s baseline status, treatment effectiveness and progression of respiratory disease with regards to chest wall mobility and respiratory muscle function. Aim To evaluate the effects of flow and volume incentive spirometer on chest expansion in CABG surgery patients. Materials and method Fifty six sample sizes were undergone CABG surgery which was randomly divided as follows: 18 subjects performed flow oriented incentive spirometer group, and other 18 subjects performed volume oriented incentive spirometer group. All of them underwent evaluations and Data was obtained by measuring chest expansion with chest exposed and with the help of an non stretchable inch tape the chest expansion was measured at three levels that is 2nd intercostal space (Axilla level), 4th intercostal space (Nipple level), and xiphoid process. Conclusion The study concluded that,” Volume incentive spirometry is more effective than Flow incentive spirometry in improving chest expansion in CABG surgery patients.”